Overview of Basic Sanitation in the Coastal Area of Sanggula Village, North Moramo Sub-district, South Konawe Regency, Southeast Sulawesi Province, Indonesia - Hartati Bahar (Journal of Health Science and Pharmacy, 2025)
Background: Basic sanitation plays a critical role in promoting a healthy environment and fulfilling public health standards. This includes the availability of clean water facilities, household latrine ownership, the condition of Wastewater Drainage Systems (SPAL), and access to solid waste disposal facilities. Preliminary observations indicate that the basic sanitation infrastructure in Sanggula Village remains inadequate and requires further attention and development. Objective: This study aims to describe the availability and condition of basic sanitation infrastructure within the community of Sanggula Village, North Moramo District, South Konawe Regency, Southeast Sulawesi Province, Indonesia. Methods: This research employed a quantitative descriptive approach, conducted in Sanggula Village, North Moramo District, South Konawe Regency, Southeast Sulawesi Province. The study population comprised 360 household heads. A proportional random sampling technique was applied, resulting in a sample of 189 households selected from four hamlets within the village. Data were analyzed using frequency distribution and presented in a descriptive narrative format. Results: The findings reveal that while basic sanitation in Sanggula Village demonstrates several positive aspects, significant disparities remain. Clean water access, latrine ownership, and SPAL conditions show relatively favorable levels. However, ownership and access to adequate waste disposal facilities are notably lower compared to the other sanitation components assessed. Conclusion: Overall, the basic sanitation status in Sanggula Village can be considered relatively adequate, yet there are critical areas particularly in waste management infrastructure that require further improvement to meet comprehensive environmental health standards. Keywords: basic sanitation, environmental health, coastal community